2018
DOI: 10.3389/fimmu.2018.00878
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingiva-Derived Mesenchymal Stem Cells Modulate Monocytes/Macrophages and Alleviate Atherosclerosis

Abstract: Atherosclerosis is the major cause of cardiovascular diseases. Current evidences indicate that inflammation is involved in the pathogenesis of atherosclerosis. Human gingiva-derived mesenchymal stem cells (GMSC) have shown anti-inflammatory and immunomodulatory effects on autoimmune and inflammatory diseases. However, the function of GMSC in controlling atherosclerosis is far from clear. The present study is aimed to elucidate the role of GMSC in atherosclerosis, examining the inhibition of GMSC on macrophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 87 publications
1
85
1
Order By: Relevance
“…The significant therapeutic effects observed in treating graft vs host disease (GVHD) and rheumatoid arthritis via a mechanism related to that of Tregs increased our interest in GMSCs. GMSCs have been shown to suppress the differentiation, frequency, activation and cytokine production of inflammatory monocytes and macrophages . Here, we demonstrated that GMSC treatment represents a promising strategy to prevent the development of IBD compared to fibroblasts.…”
Section: Discussionmentioning
confidence: 78%
“…The significant therapeutic effects observed in treating graft vs host disease (GVHD) and rheumatoid arthritis via a mechanism related to that of Tregs increased our interest in GMSCs. GMSCs have been shown to suppress the differentiation, frequency, activation and cytokine production of inflammatory monocytes and macrophages . Here, we demonstrated that GMSC treatment represents a promising strategy to prevent the development of IBD compared to fibroblasts.…”
Section: Discussionmentioning
confidence: 78%
“…Human gingival derived MSCs (GMSCs) are another member of MSCs and have been considered as a promising source of MSCs for their ease and safe isolation and fast proliferation properties [49]. In line with other studies, our group recently observed that infusion of GMSCs can also alleviate atherosclerosis in ApoE −/− Mice [17]. In this study, atherosclerotic models were built by feeding 8 week old male ApoE −/− mice a high fat diet for 12 weeks, and GMSCs (2X10 6 ) were administrated every three weeks from the first day of high fat diet for a total of three times.…”
Section: Human Gingival-derived Mscs In Atherosclerosismentioning
confidence: 54%
“…Due to their multiple differentiation capabilities, inflammatory and immune modulation function, MSCs have been explored as an attractive therapeutic agent in various diseases including allergic conjunctivitis, acute lung injury, myocardial infarction, allergic rhinitis, Alzheimer's disease, and type 1 diabetes [9][10][11][12][13][14][15]. In light of the critical role inflammatory processes have in the initiation and progression of atherosclerosis, our group and others have transfered MSCs to atherosclerotic animal models revealing MSCs were able to alleviate atherosclerosis [16][17][18]. These results are important for further investigation into its potential clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the control group where atherosclerotic mice models were fed with western diet, atherosclerotic plaque size and lipid deposition were significantly reduced in mice after BMSC transplantation. Moreover, the number of activated macrophages with inflammatory phenotype and macrophage-derived foam cells was all reduced [61].…”
Section: Bmscs Affect Macrophages Polarizationmentioning
confidence: 98%